The role of Dryland Agricultural Research Institute in drought mitigation in Iran - Ghaffari A. (Economics of drought and drought preparedness in a climate change context, 2010)
Although drought is a natural hazard, the term drought management and action plans imply that human intervention can reduce vulnerability and impacts. To be successful in this endeavor, many disciplines must work together in tackling the complex issues associated with detecting, responding to, and preparing for the inevitability of future events. Disaster management, of which drought management is a subset, requires scientists and policy makers to focus on both the protection and recovery/rehabilitation of drought. In the past, the emphasis in disaster management has been placed largely on the response and recovery portion of drought management, with little or no attention to mitigation, preparedness, and prediction and monitoring. The Dryland Agricultural Research Institute (DARI), in Iran mainly focused on the breeding crops for drought tolerance, soil management to conserve moisture (minimum tillage, crop rotation, etc.), supplementary irrigation, water harvesting, and agro-ecological zoning considered as basic activities that should be strengthened to cope with drought in the future.
2. International Conference on Drought Management, 2010/03/04-06, Istanbul (Turkey)